The social Aspect for homeland and citizen ship in Khari Al-Den Al-zirikil’s poetry (Journal of Hama University, 2024)
This research deals with the social dimension of homeland and citizshp in the poetry of the Syrian poet" Khair AI-Deen AL Zirikil`s" who struggalt for the freedom of his country, so he was.Sentenced to death more than once. In his poetry, it looks like the situation of the a ffliacated people during the french mandate over syria in 1920. We found in his poetry sufficient material for study in quantity and quality. His national struggle was the catalyst for research to statement the motives of citizen ship and her reasons, and how to fight for freedom. The research will provide a comprehensive study of his national struggle with its social dimension based on the semiotic approach, to meet the various dimension of this phenomenon. It will classify and evaluate it to provide a detailed picture of it.